Retrospective Analysis of the Computed Tomography Pulmonary Angiogram Utilization Patterns in the Emergency Department. Issue 4 (November 2019) - Ferguson, Craig; Low, Gavin; Fung, Christopher
Objectives: Guidelines and high-quality studies recommend using clinical decision-making (CDM) tools over clinical gestalt when evaluating a patient for pulmonary embolism. The purpose of this study is to investigate our computed tomography pulmonary angiogram (CTPA) utilization patterns and identify causal factors. Methods: A retrospective cohort study of CTPA studies ordered by emergency physicians in January, April, July, and October 2017 was undertaken. All necessary information to categorize patients by Wells' score, revised Geneva score, and pulmonary embolism rule-out criteria (PERC) was collected. In addition, various bloodwork, chest radiograph, and computed tomography results were collected. This data was analysed by the Pearson chi-square test or Fisher's exact test for categorical data and independent-samples t test for continuous variables. Results: A total of 510 CTPA studies were performed, with a mean age was 61.6 and a 50.6% female population. 136 studies (26.7%) failed to appropriately follow any CDM tool. CDM tool failure rate was dependent on whether the study was ordered from a community (14.9%) or tertiary hospital (University of Alberta Hospital, 27.9% and Royal Alexandra Hospital, 24.6%) ( P = .038). Of these 136 studies, 31 were low/moderate risk and the d-dimer was negative. The remainder were either PERC-negative or low/moderate risk without d-dimer performed. The cumulative positive pulmonary embolism rate was 12.5%. With utilization of a CDM tool, the positive pulmonary embolism rate was 15.0%, compared to 5.9% when using gestalt ( P = .026). Conclusions: This study confirms a high rate of CDM tool use failure, and a higher positive CTPA rate for CDM tools compared to clinical gestalt.